Drying kinetics and quality of uvaia (Hexachlamys edulis (O. Berg)) powder obtained by foam-mat drying - Branco, Ivanise Guilherme [UNESP]; Kikuchi, Thatyana Tammy [UNESP]; Argandoña, Eliana Janet Sanjinez; Moraes, Izabel Cristina Freitas; Haminiuk, Charles Windson Isidoro (Oxford University Press (OUP), 2016)
Investigations were carried out to study the influence of the formulation on the drying characteristics and the final quality of foam-mat-dried uvaia pulp powder, such as total phenolic content, carotenoids and antioxidant activity. Two formulations were developed (one with 3.5% albumin (Alb.), 0.25% carboxymethylcellulose (CMC) and 0.25% xanthan gum (XG), and the other containing only 7% albumin) and dried at 60 and 70 °C. Drying kinetics showed only a falling rate at both temperatures and formulations. Mathematical models were fitted to the experimental data to describe the drying kinetics. The Page model provided the best description of the foams. The higher temperatures reduced the drying time and increased the effective diffusivity. Compared with the fresh pulp, the uvaia powder at 70 °C exhibited decreased antioxidant activity, total phenolics and carotenoids contents.
Keywords: Antioxidant activity; effective diffusivity; foam-mat drying; Hexachlamys edulis (O. Berg); Page model; uvaia